What, when & how to learn about sex: the narratives of students with disabilities - Mohamad Diah, Nurazzura; Samsudin, Suhaiza (Atlantis Press, 2020)
Sexual health is fundamental to the overall health and well-being of individuals, couples and families, and to the social and economic development of communities and countries (WHO, 2020).Young people with disabilities are not automatically asexual.